Derivational Morpheme in "Khanh Vy Tran's Speech On TEDx Talk" Talk Show - Jihan Herina; Diana Zuriati (Enlighted Journal, 2023)
This research analyzed the derivational morpheme in "Khanh Vy Tran's Speech On TEDx Talk" talk showâ€. The researchâ€™s purpose was to find out the derivational morpheme found in "Khanh Vy Tran's Speech On TEDx Talk" and also describe the lexical changes happened of the derivational morpheme found. The researcher used several theories about the derivational morpheme and the lexical changes to support the research as example from Fromkin, Yule and Katamba. The researcher used the descriptive qualitative method to analyze and to describe the collected data. The researcher used the video of Khanh Vy Tran's speech which was downloaded from YouTube and transcribed into transcript as the core data of the analysis. To support the analysis, the researcher used the Oxford dictionary and articles related to the topic. As the result, the researcher found total of 39 words of derivational morpheme. The derivational morpheme was divided by its suffix based on the lexical changes attached of the words, and it was found that 18 words in verb into noun category, 12 words in adjective into adverb category; 2 words adjective into noun category, 1 word adjective into adjective category, 3 words in noun into adjective category, and 3 words in noun into noun category. It could be concluded that the derivational morpheme in the speech was highly used by Khan Vy Tran.